PELUANG DAN TANTANGAN GADAI EMAS (RAHN) DI INDONESIA: SEBUAH TINJAUAN KONSEPTUAL - ERMAWATI, TITIN (Jurnal Akuntansi AKUNESA, 2013)
Gold pawn (rahn) is needed as a new alternative for micro financing in Islamic financial institutions. This study aims to analyze opportunities and challenges of gold pawn (rahn) in Indonesia after release of Bank Indonesia Circular Letter No.14/7/DPbS about qardh gold-backed products for Islamic Bank and Islamic Business Unit. Gold pawn can be alternative for consumers to get easy money and have a fast process.Keywords: Gold pawn, Rahn, opportunities, challenges and Bank Indonesia Circular Letter No. 14/7/DPbS